2023
DOI: 10.1101/2023.04.18.537286
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved Metabolic Regulator ArcA Responds to Oxygen Availability, Iron Limitation, and Cell Envelope Perturbations during Bacteremia

Abstract: Bacteremia, a systemic infection associated with severe clinical outcomes, is often caused by Gram-negative facultative anaerobes. ArcAB, a two-component regulatory system that represses aerobic respiration, is a key mediator of metabolic adaptation for such bacteria. Using targeted mutational analysis informed by global genetic screens, we identified thearcAgene as promoting fitness ofKlebsiella pneumoniae,Citrobacter freundii, andSerratia marcescensbut notEscherichia coliin a murine model of bacteremia. Engi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…ArcA is a global gene regulator of aerobic respiration that contributes to the maintenance of a proton motive force when oxygen is available. In a recent study [119], we constructed deletion mutants in the aerobic respiration control sensor arcA across four species and confirmed that ArcA is a bacteremia-fitness factor in K. pneumoniae, C. freundii, and S. marcescens but not E. coli. ArcA is conserved across the Enterobacterales and clearly contributes to fitness in a murine bacteremia model [119].…”
Section: Shikimate Biosynthesismentioning
confidence: 64%
See 1 more Smart Citation
“…ArcA is a global gene regulator of aerobic respiration that contributes to the maintenance of a proton motive force when oxygen is available. In a recent study [119], we constructed deletion mutants in the aerobic respiration control sensor arcA across four species and confirmed that ArcA is a bacteremia-fitness factor in K. pneumoniae, C. freundii, and S. marcescens but not E. coli. ArcA is conserved across the Enterobacterales and clearly contributes to fitness in a murine bacteremia model [119].…”
Section: Shikimate Biosynthesismentioning
confidence: 64%
“…In a recent study [119], we constructed deletion mutants in the aerobic respiration control sensor arcA across four species and confirmed that ArcA is a bacteremia-fitness factor in K. pneumoniae, C. freundii, and S. marcescens but not E. coli. ArcA is conserved across the Enterobacterales and clearly contributes to fitness in a murine bacteremia model [119]. Because this regulator, along with ArcB, mediates transition from aerobic to anaerobic growth, mutants in arcA do not grow well under anaerobic conditions.…”
Section: Shikimate Biosynthesismentioning
confidence: 64%